(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Improvement of 1VPU fiber cleaner Use of 1VPU type fiber cleaning machines in fiber cleaning technology of cotton cleaning enterprises. To increase the efficiency of fiber cleaning, a new design cassette-type column grid and fiber guide were developed for the 1VPU machine